Neonatology nurses’ knowledge about „The newborn program of early stimulation and development care” - Brosowska, Beata; Kowalczyk, Renata; Glińska, Jolanta (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Background. “Newborn program of early stimulation and development care” has many advices that are useful for easier work with a premature. The program shows the ways of care, and conditions that must be done for comfort of little patient and for achievement of the highest level of development despite its health problem and hospitalization. Aim. The objective of the research was to evaluate nurses’ knowledge about “newborn program of early stimulation and development care” Material and methods. The research was in 2006, with 30 nurses who worked in 2 Neonatal Units. The questionnaire elaborated by authors was used in the research. Results and conclusions. Neonatal nurses have sufficient knowledge about “newborn program of early stimulation and development care”. They know main rules of program, what are: „artificial nights”, „baby nests”, „kangaroo care”, how to do nursing procedures at children, how to touch them, what are the reasons of children’s deafness. Besides nurses know that is necessary to eliminate bad impulses, they know that the program after few modifications can be used with all children. Unfortunately there are some lacking of nurses’ knowledge.